SOME FEATURES OF THE QUALIFICATION OF CRIMINAL OFFENSES IN THE FIELD OF LABOR PROTECTION, AS WELL AS THEIR PREVENTION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this article, the author explores some problems of qualifying criminal acts in the field of labor protection, considers various options for the events of criminal offenses with modeling examples, analyzes the objective side of the actions (inaction) of guilty persons in relation to the rules of industrial safety and labor protection. The content of cases co-infliction is also revealed, the need to distinguish between the actions of suspected and accused persons is substantiated, and in addition, attention is focused on the features of prevention of this types of offenses.
Keywords: Labor, Labor relations, violations of labor protection rules, industrial injuries, criminal liability, reckless coinfliction, crime prevention.